The 2030 agenda and the sustainable development goals : an opportunity for Latin America and the Caribbean (UN ECLAC SantiagoCL, 2016)
Aims to assist and support countries of Latin America and the Caribbean in the process of implementation and follow-up to the Agenda and the Sustainable Development Goals, placing its analytical, technical and human capacities at their disposal.
Keywords: SUSTAINABLE DEVELOPMENT